2011
DOI: 10.1017/s0022029911000367
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the inactivation of the natural microbiota of milk processed by pulsed electric fields and cross-flow microfiltration

Abstract: Prior to processing milk and cream were standardised and homogenised. Skim milk was cross-flow microfiltered (CFMF) prior to treatment with pulsed electric fields (PEF) or high temperature short time (HTST) pasteurization. The effect of temperature of the skim milk and product composition on the efficacy of PEF treatment was determined. The electrical conductivity of the product was related to fat and solids content and increased 5% for every g/kg increase of solids and decreased by nearly 0·7% for every g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…2(b). Due to the high electrical conductivity of the liquid food products [15], [16], the processing chamber acts as a purely resistive load. As a result, the transient current would be expected to follow first-order behavior during the capacitor discharge.…”
Section: A Pef Processing Setupmentioning
confidence: 99%
“…2(b). Due to the high electrical conductivity of the liquid food products [15], [16], the processing chamber acts as a purely resistive load. As a result, the transient current would be expected to follow first-order behavior during the capacitor discharge.…”
Section: A Pef Processing Setupmentioning
confidence: 99%
“…A microfiltração também tem sido utilizada em combinação com o processo de pulsos elétricos e se conseguiu uma redução de microrganismos mesófilos maior que 4,0 ciclos log, comparável ao processo de microfiltração seguido de pasteurização (RODRÍGUES-GONZÁLEZ et al, 2011).…”
Section: Uso Da Microfiltração Para Estender a Vida De Prateleira Do unclassified
“…Commercially available thermal processing methods promise a high degree of microbial safety but can adversely affect other food properties such as color and volatile compounds. Several studies have demonstrated a comparable impact of PEF and MF processes on microbial inactivation in foods [ 13 , 14 , 15 , 16 , 17 ]. Milk has its natural color due to the reflectance of light by dispersed milk fat globules, proteins, and natural milk pigments like riboflavin and carotenoids [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microfiltration is one of the non-thermal technologies that have been commercially allowed for extending shelf life of milk, although its use as a stand-alone treatment is restricted due to regulatory requirements [ 25 ]. Based on microbiological data, previous studies have indicated that the safety of skim milk processed with a combination of PEF and MF is comparable to that achieved by HTST pasteurization [ 13 , 17 ], potentially representing a non-thermal alternative to the well-established heat pasteurization. However, the effect of this novel process on color and volatile compounds has not been determined.…”
Section: Introductionmentioning
confidence: 99%